(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The essay analyzes two historical periods, both significant for what concerns the extension and radicalization of violence in Mexico: the so-called guerra sucia, that took place in the ’60-‘70’s, and the current narcoguerra. The aim of the research is to outline causes and subjects involved in the outbursts, and to explain how violence is absorbed, internalized and understood - or misunderstood - by society, according to the different narration that journalism makes of it. Through the analysis of the role of press during the guerra sucia, of some examples of violence against civilians that took place in the last years, and thanks to the testimony of some well-known Mexican journalists - this study provides a description of journalism as an instrument that contributes to social change and to the achievement of common good. Journalism cannot replace the law, but in some cases, as the Mexican one, it can fill up the gaps left by inadequate systems of justice, protecting the interests of society by denouncing crimes and violations of human rights.